2018
DOI: 10.3892/etm.2018.5782
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the polyphenol composition BP‑C3 on haematological and intestinal indicators of 5‑fluorouracil toxicity in mice

Abstract: Abstract. BP-C3 is a formulation, which comprises lignin-derived polyphenolic composition of benzenepolycarboxylic acids (BP-Cx-1) with iron complex, selenium, ascorbic acid and retinol, and possesses geroprotective activity. The present study examined the effect of BP-C3 (80 mg/kg, administered 18 times in total by gavage) on the development of haematological and intestinal manifestations of toxicity following 5-fluorouracil (5-FU; 150 mg/kg, administered once via intravenous injection) administration in outb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
1
10
0
5
Order By: Relevance
“…In the present study, BP-C3 was less efficient in protecting laboratory animals from the hematological toxicity induced by CPA than in the previously reported study where BP-C3 was administered to animals treated with 5-fluorouracil. 3 The results of our study confirm the earlier reported antitumor effect of polyphenolic compounds by demonstrating the antitumor activity of the lignin-derived polyphenolic composition BP-C3 in male mice with soft tissue sarcomas. BP-C3 does not have a significant effect on the proliferative rate of the soft tissue sarcomas, while the addition of BP-C3 to a CPA regimen allows a decrease in tumor vasculature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, BP-C3 was less efficient in protecting laboratory animals from the hematological toxicity induced by CPA than in the previously reported study where BP-C3 was administered to animals treated with 5-fluorouracil. 3 The results of our study confirm the earlier reported antitumor effect of polyphenolic compounds by demonstrating the antitumor activity of the lignin-derived polyphenolic composition BP-C3 in male mice with soft tissue sarcomas. BP-C3 does not have a significant effect on the proliferative rate of the soft tissue sarcomas, while the addition of BP-C3 to a CPA regimen allows a decrease in tumor vasculature.…”
Section: Discussionsupporting
confidence: 90%
“…In our previous studies, we have demonstrated the activity of BP-C3 against the hematological toxicity induced by 5-fluorouracil: BP-C3 prevented the development of anemia in SHR mice exposed to 5-fluorouracil. 3…”
Section: Results Of Study On Assessment Of Cpa Efficacy and Hematologmentioning
confidence: 99%
“…C19 significantly decreased tumor growth and much more efficient than the currently used chemotherapeutic agent 5-Fu, which also showed significant toxicity in mice [ 36 ]. 5-Fu is effective against some types of intestinal cancers such as colorectal cancer where it is primarily associated with tissue damaging and regenerating effects in the gastrointestinal mucosa [ 37 ]. FOLFOX4 is a combination chemotherapy regimen involving administration of oxaliplatin in combination with 5-FU and leucovorin; this regimen is reportedly active in patients who have been previously treated with 5-FU alone or in combination with leucovorin.…”
Section: Discussionmentioning
confidence: 99%
“…BP-C3 is a composition of BP-Cx-1 with iron complex, selenium, ascorbic acid, and retinol. It exhibits geroprotective activity [ 19 ] and reduces 5-fluorouracil toxicity in mice by accelerating recovery of leukopoiesis and protecting small intestine epithelium [ 20 ].…”
Section: Introductionmentioning
confidence: 99%